THE DEVELOPMENT OF ESG REPORTING IN THE FINANCIAL SECTOR THROUGH CSRD IN THE EU - Jil Anjou Lavinia Saxena (2024)
Over the last decades, especially in the last ten years, the integration of sustainability has become increasingly relevant in the business world. In the financial sector, Environmental, Social, and Governance (ESG) has emerged as a criterion for sustainability. Thus, ESG reporting has developed into an essential practice for companies to demonstrate their commitment to sustainability. The European Union (EU) transitioned from voluntary to mandatory ESG reporting under the Non-Financial Reporting Directive (NFRD) in 2014. The NFRD and its flexibility in not implementing a mandatory reporting standard, however, led to several major issues, which is why it was replaced by the Corporate Sustainability Reporting Directive (CSRD). With the CSRD, the European legislator has established a milestone in ESG reporting and completed a key project of the sustainable finance regulation framework. In the future, more European and even some non-European companies will be obliged to prepare and publish standardized, digitalized, and externally audited sustainability reports in their management reports. This thesis seeks to look at how voluntary and mandatory ESG reporting was shaped by the NFRD and its amendment into the CSRD in the European Union. The research aims to assess whether the CSRD has managed to overcome the challenges of the NFRD by analyzing the new requirements, particularly in harmonizing ESG reporting standards, addressing the absence of a unified sustainability reporting framework, and focusing on the financial sector due to its essential role in financing but also guiding the EU's goals of sustainable transition and development.